Nutraceuticals for the treatment of sarcopenia in chronic liver disease. (February 2021) - Hey, Penelope; Gow, Paul; Testro, Adam G.; Apostolov, Ross; Chapman, Brooke; Sinclair, Marie
Summary: Background and aims: Sarcopenia, defined as loss of muscle mass, strength and function, is associated with adverse clinical outcomes in patients with cirrhosis. Despite improved understanding of the multifaceted pathogenesis, there are few established therapies to treat or prevent muscle loss in this population. This narrative review examines the available literature investigating the role of nutraceuticals for the prevention or treatment of muscle wasting in chronic liver disease. Methods: A comprehensive search or Medline and PubMED databases was conducted. Reference lists were screened to identify additional articles. Results: A number of nutritional supplements and vitamins target the specific metabolic derangements that contribute to sarcopenia in cirrhosis including altered amino acid metabolism, hyperammonaemia and inflammation. Branched chain amino acid (BCAA) supplementation has proposed anabolic effects through dual pathways of enhanced ammonia clearance and stimulation of muscle protein synthesis. l -carnitine also has multimodal effects on muscle and shows promise as a therapy for muscle loss through anti-inflammatory, antioxidant and ammonia lowering properties. Other nutraceuticals including l -ornithine l -aspartate, omega-3 polyunsaturated fatty acids and zinc and vitamin D supplementation, may similarly have positive effects on muscle homeostasis, however further evidence to support their use in cirrhotic populations is required. Conclusion: Nutraceuticals offer a promising and likely safe adjunct to standard care for sarcopenia in cirrhosis. While there is most evidence to support the use of BCAA and l -carnitine supplementation, further well-designed clinical trials are needed to elucidate their efficacy as a therapy for muscle loss in this population.